Answer:
x - y = - 5
Explanation:
Given the 2 equations
2x + 3y - 10 = 0 ( add 10 to both sides )
2x + 3y = 10 → (1)
3x = 2y - 11 ( subtract 2y from both sides )
3x - 2y = - 11 → (2)
Multiplying (1) by 3 and (2) by - 2 and adding will eliminate the term in x
6x + 9y = 30 → (3)
- 6x + 4y = 22 → (4)
Add (3) and (4) term by term to eliminate the x- term
13y = 52 ( divide both sides by 13 )
y = 4
Substitute y = 4 into either of the 2 equations and evaluate for x
Substituting into (1)
2x + 3(4) = 10
2x + 12 = 10 ( subtract 12 from both sides )
2x = - 2 ( divide both sides by 2 )
x = - 1
Thus
x - y = - 1 - 4 = - 5